Integrating Local Cultural Values in Character Formation and Academic Achievement - Widia Yusuf, Ilham Agustian; Habibie, Dienha; Basith, Fardan Abdul; Sarbini, Ahmad (IAIN Manado, 2025)
This research aims to explore the role of local cultural values in shaping Student character and learning achievement at Tri Daya Budi Vocational School, Majalengka. In context Increasingly rapid globalization, the importance of character education that is rooted in culture local is becoming increasingly relevant. Through a qualitative approach, this research identifies various local cultural values that can be integrated into the educational curriculum, as well its impact on character development and student academic achievement. Research result shows that the introduction and application of local cultural values is not only helpful students recognize and value their cultural identity, but also encourage attitudes tolerance and innovation. Thus, education prioritizes cultural values Local communities have the potential to create a generation that is intelligent, has strong character and is able to face global challenges without losing their identity. This research is expected to provide contribution to the development of more relevant and sustainable educational programs in Indonesia.